Managing African elephants for ivory production - Tom Pilgram; David Western (Pachyderm)
The decline in number of African elephants is a disadvantage to those involved in the ivory trade, who in the long run suffer financial losses. In this light, those involved in the trade should be interested in management strategies that will preserve both African elephant numbers and ivory production at a high level for a foreseeable future. The article discusses general types of management strategies and their effects on long term ivory production are expressed as regulation of killing patterns. Results obtained through a computerized simulation model are discuss.